2018
DOI: 10.1007/s10995-018-2438-9
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Infant Confinement Equipment in Community-Based Child Care Centers: An Analysis of Centers Participating in a Statewide Quality Rating and Improvement System

Abstract: Objectives Although infants increasingly spend time in community-based child care centers, little attention has been paid to their physical activity experiences while in group care. In particular, the use of devices to restrict infant mobility, such as bouncy seats, high chairs, cribs, and stationary activity centers, has received little attention in the physical activity literature. The current study examines the presence and use of these confinement devices in infant classrooms. Methods A secondary analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…7,29,[35][36][37] Two recent studies suggest that the use of restrictive equipment is prevalent in ECE settings. 33,38 However, we found that just over half of states had regulations limiting the use of strollers, swings, and other types of confining equipment. This could be an important area for improvement, as states consider updates to their regulations.…”
Section: Discussionmentioning
confidence: 89%
“…7,29,[35][36][37] Two recent studies suggest that the use of restrictive equipment is prevalent in ECE settings. 33,38 However, we found that just over half of states had regulations limiting the use of strollers, swings, and other types of confining equipment. This could be an important area for improvement, as states consider updates to their regulations.…”
Section: Discussionmentioning
confidence: 89%
“…Caregivers may place infants in seating devices (e.g., swings, car seats, bouncy seats) for reasons of convenience, safety, soothing, and entertainment-for example, to allow the caregiver to engage in activities that are more successfully or safely approached without holding an infant (e.g., showering; cooking on a hot stove) or to provide time for independent infant exploration (e.g., of sensory activities in an exersaucer). Studies have reported widespread use in both home (Abbott & Bartlett, 2001;Callahan & Sisler, 1997;Fay et al, 2006;Siddicky et al, 2020) and group childcare settings (Hallam et al, 2018). In one study, 90% of participants with two or more children reported daily use of walkers, exersaucers, or jumpers (Fay et al, 2006).…”
Section: Infant Seating Device Use and Language Exposurementioning
confidence: 99%
“…For example, differences may arise from sleeping practices (reduced use of co-sleeping, i.e., not sharing a bed with caregiver) or infant care methods that are more prevalent in Western societies such as feeding of infant formula and use of infant equipment (Bigelow & Williams, 2020), which may reduce physical contact between parent and child. Studies have reported widespread use of infant equipment, for example, both at home and in childcare settings in the U.S. (Fay et al, 2006;Hallam et al, 2018;Siddicky et al, 2020). Use of bouncers, car seats, and infant swings can help to soothe and entertain children as well as allow caregivers to engage in other tasks (e.g., cooking, showering), thus providing a safe and convenient way for caregivers to continue daily activities made more difficult while holding or wearing an infant.…”
Section: Cultural Variation In Infant Carryingmentioning
confidence: 99%
“…Use of infant equipment (e.g., bouncers, car seats, and infant swings), provides a convenient way for caregivers to engage in other activities, while keeping their child entertained and safe. Widespread use of these devices has been reported, particularly in Western settings such as the U.S. (Fay et al, 2006;Hallam et al, 2018;Siddicky et al, 2020), with implications for caregiver-child proximity, both increasing distance and duration of time spent apart (Little et al, 2019;Maudlin et al, 2012). The relative increase in the availability and use of infant holding devices or equipment (e.g., bouncers, highchairs) may impact rates of baby carrying/wearing in Western settings, with potential implications (1984) Physical distance between mother and infant measured during mother-child interactions and coded (for each minute) on a 3-point scale representing (1) mother-child >2 feet apart (2) <2 feet apart, or (3) in physical contact.…”
Section: Use Of Infant Equipmentmentioning
confidence: 99%